Architect's pocket book of kitchen design / Charlotte Baden-Powell - Baden-Powell, Charlotte1936-
"This book is of use to the student as well as the experienced practitioner. It sets out everything needed to design a domestic kitchen including planning, ergonomics, services, appliances, cabinets and finishes. It also deals with the needs of disabled people, safety and green issues."